Exome sequencing reveals a novel CWF19L1 mutation associated with intellectual disability and cerebellar atrophy. Issue 6 (26th March 2016) - Evers, Christina; Kaufmann, Lilian; Seitz, Angelika; Paramasivam, Nagarajan; Granzow, Martin; Karch, Stephanie; Fischer, Christine; Hinderhofer, Katrin; Gdynia, Georg; Elsässer, Michael; Pinkert, Stefan; Schlesner, Matthias; et al.
Abstract : Intellectual disability (ID) with cerebellar ataxia comprises a genetically heterogeneous group of neurodevelopmental disorders. We identified a homozygous frameshift mutation in CWF19L1 (c.467delC; p.(P156Hfs*33)) by a combination of linkage analysis and Whole Exome Sequencing in a consanguineous Turkish family with a 9‐year‐old boy affected by early onset cerebellar ataxia and mild ID. Serial MRI showed mildly progressive cerebellar atrophy. Absent C19L1 protein expression in lymphoblastoid cell lines strongly suggested that c.467delC is a disease‐causing alteration. One further pregnancy of the mother had been terminated at 22 weeks of gestation because of a small cerebellum and agenesis of corpus callosum. The homozygous CWF19L1 variant was also present in the fetus. Postmortem examination of the fetus in addition showed unilateral hexadactyly and vertebral malformations. These features have not been reported and may represent an expansion of the CWF19L1 ‐related phenotypic spectrum, but could also be due to another, possibly autosomal recessive disorder. The exact function of the evolutionarily highly conserved C19L1 protein is unknown. So far, homozygous or compound heterozygous mutations in CWF19L1 have been identified in two Turkish siblings and a Dutch girl, respectively, affected by cerebellar ataxia and ID. A zebrafish model showed that CWF19L1 loss‐of‐function mutations result in abnormal cerebellar morphology and movement disorders. Our report corroborates that loss‐of‐function mutations in CWF19Ll lead to early onset cerebellar ataxia and (progressive) cerebellar atrophy. © 2016 Wiley Periodicals, Inc.